Postoperative kidney injury does not decrease survival after liver transplantation - Fonseca-Neto,Olival Cirilo Lucena da (2012)
PURPOSE: To explore the effect of acute kidney injury (AKI) on long-term survival after conventional orthotopic liver transplantation (OLT) without venovenous bypass (VVB). METHODS: A retrospective cohort study was carried out on 153 patients with end-stage liver diseases transplanted by the Department of General Surgery and Liver Transplantation of the University of Pernambuco, from August, 1999 to December, 2009. The Kaplan-Meier survival estimates and log-rank test were applied to explore the association between AKI and long-term patient survival, and multivariate analyses were applied to control the effect of other variables. RESULTS: Over the 12.8-year follow-up, 58.8% patients were alive with a median follow-up of 4.5-year. Patient 1-, 2-, 3- and 5-year survival were 74.5%, 70.6%, 67.9% and 60.1%; respectively. Early postoperative mortality was poorer amongst patients who developed AKI (5.4% vs. 20%, p=0.010), but long-term 5-year survival did not significantly differed between groups (51.4% vs. 65.3%; p=0.077). After multivariate analyses, AKI was not significantly related to long-term survival and only the intraoperative transfusion of red blood cells was significantly related to this outcome (non-adjusted Exp[b]=1.072; p=0.045). CONCLUSION: The occurrence of postoperative acute kidney injury did not independently decrease patient survival after orthotopic liver transplantation without venovenous bypass in this data from northeast Brazil.